Factors Influencing Physician Counseling on Cardiovascular Risk - Val Rakita; Carol J. Homko; Abul Kashem; Nabeel Memon; Alfred A. Bove (SAGE Publishing, 2016)
Background and Importance: A significant reduction in cardiovascular disease (CVD) mortality is related to aggressive management of modifiable CVD risk factors. Therefore, patients at increased risk for CVD should not only benefit from standard pharmacotherapy but also from counseling regarding lifestyle behavioral changes. Objective: To determine the patient factors that influence provision of cardiovascular risk reduction counseling from physicians, as well as the frequencies of counseling. Design, Setting, and Participants: Secondary analysis of a prospective, randomized trial among an underserved inner-city and rural population (n = 388) with a 10% or greater CVD risk (Framingham 10-year risk score). Subjects were followed for 1 year and were seen for quarterly assessments, which included evaluation of weight, blood pressure, lipid, and glucose status. At each of the 4 quarterly visits, subjects were asked if their physician had discussed or made recommendations regarding lifestyle behaviors, specifically diet, weight loss, and exercise. Results: The average patient age was 61.3 ± 10.1 years, average A1c was 6.7 ± 1.6%, average total cholesterol was 201 ± 44 mg/dL. The average body mass index (BMI) was 31.8 ± 6.4 kg/m 2 , and the average blood pressure was 146 ± 18/82 ±11 mm Hg. Using binary logistic regression analysis, BMI ( P < .025) was the only clinical factor related to physician lifestyle counseling. All other risk factors showed no statistical relationship. Conclusion: The data indicate that BMI is the major factor associated with whether or not physicians provide counseling regarding nutrition and weight loss. Physicians may be missing important opportunities to influence behavior in patients at high risk for CVD by limiting their focus to obese patients.